Using technologies to evaluate response style in the competency crisis recommendations for evaluators - Danzer, Graham (The journal of forensic psychiatry & psychology, 2024)
It is possible that a portion of the competency crisis may be due to some defendants being misclassified as incompetent, secondary to evaluations of questionable thoroughness and quality, and perhaps over-reliance on interviews and lesser acquisition of collateral data. Meanwhile, a review of descriptive statistics suggests that, as criminal penalties have become increasingly harsh, requests for competency evaluations have proportionately increased. Thus, there is a risk that lengthy waiting lists, mounting time pressures, and attorney tactics may push evaluators in the direction of expediency, possibly at the expense of higher quality forensic work. Evaluators may therefore consider acquiring and perhaps more significantly relying upon relevant collateral informational sources, including police recorded interviews, jail recorded calls, social media content, and prior court records. While an evaluation of present mental state does not necessarily require significant background data, better use of technologies in an evaluation of competency may provide a more objective representation of competency-relevant, mental health-related history. So doing may help to solve a portion of the competency crisis that may be due to evaluations including inadequate collateral data. Best practice approaches, anecdotes, and limitations are presented.